Method for evaluating interfacial resistances of thermoelectric devices using I-V measurement. (December 2018) - Kim, Dong Hwan; Kim, Cham; Kim, Jong Tae; Yoon, Duck Ki; Kim, Hoyoung
Highlights: An evaluation method of the interfacial resistance of a TEG device is proposed. Analytic expressions for the VOC and ISC have been derived. The electrical contact resistance of a thermoelectric device calculated. The evaluation method can be used as an index to improve the soldering process. Abstract: Research on the methodology for predicting and analyzing the performance of a thermoelectric device (TED) can offer various possibilities for enhancing its energy conversion characteristics. In this work, the methodology to determine the electrical contact resistance and the interfacial thermal resistance of a TED was studied. Based on one-dimensional heat transfer equations of power generation mode that includes electrical contact resistance and interfacial thermal resistance, we derived explicit expressions for the open circuit voltage and the short circuit current as the limiting cases of the external electrical load. The measurements of the open circuit voltage and the short-circuit current of TED were carried out for various thermal interface materials (TIMs) between the TED and heat reservoirs under varying compressive forces. The electrical contact resistance and the interfacial thermal resistance of a TED were determined by matching the measured values of the open circuit voltage and the short circuit current of a TED to the results of the analytic model. The electrical contact resistivity of the TED tested was approximately 3 × 10 −9 Ωm 2, irrespective of the compressive force, the hot-side temperature, and the TIMs. The interfacial thermal resistance varied sensitively with the TIMs and decreased with the compressive forces.